Carbon Dots as a New Class of Diamagnetic Chemical Exchange Saturation Transfer (diaCEST) MRI Contrast Agents. Issue 29 (24th June 2019) - Zhang, Jia; Yuan, Yue; Gao, Minling; Han, Zheng; Chu, Chengyan; Li, Yuguo; van Zijl, Peter C. M.; Ying, Mingyao; Bulte, Jeff W. M.; Liu, Guanshu
Abstract: While carbon dots (C‐dots) have been extensively investigated pertaining to their fluorescent, phosphorescent, electrochemiluminescent, optoelectronic, and catalytic features, their inherent chemical exchange saturation transfer magnetic resonance imaging (CEST MRI) properties are unknown. By virtue of their hydrophilicity and abundant exchangeable protons of hydroxyl, amine, and amide anchored on the surface, we report here that C‐dots can be adapted as effective diamagnetic CEST (diaCEST) MRI contrast agents. As a proof‐of‐concept demonstration, human glioma cells were labeled with liposomes with or without encapsulated C‐dots and implanted in mouse brain. In vivo CEST MRI was able to clearly differentiate labeled cells from non‐labeled cells. The present findings may encourage new applications of C‐dots for in vivo imaging in deep tissues, which is currently not possible using conventional fluorescent (near‐infrared) C‐dots. Abstract : Think differently : Metal‐free carbon dots (C‐dots) can be used as magnetic resonance imaging (MRI) agents owing to the chemical exchange of surface‐anchored protons with water. This inherent chemical exchange saturation transfer (CEST) magnetic resonance property of C‐dots enables them to be visualized in vivo in deep tissues.